Immunization with Recombinant TcdB-Encapsulated Nanocomplex Induces Protection against Clostridium difficile Challenge in a Mouse Model - Liu, Yi-Wen; Chen, Yu-Hung; Chen, Jenn-Wei; Tsai, Pei-Jane; Huang, I-Hsiu (Frontiers in Microbiology, 2017)
Clostridium difficile is considered to be one of the major cause of infectious diarrhea in healthcare systems worldwide. Symptoms of C. difficile infection are caused largely by the production of two cytotoxins: toxin A (TcdA) and toxin B (TcdB). Vaccine development is considered to be desirable as it would decrease the mounting medical costs and mortality associated with C. difficile infections. Biodegradable nanoparticles composed of poly-γ-glutamic acid (γ-PGA) and chitosan have proven to be safe and effective antigen delivery system for many viral vaccines. However, few studies have utilized this efficient antigen carrier for bacterial vaccine development. In this study, we eliminated the toxin activity domain of toxin B by constructing a recombinant protein, rTcdB consists of residues 1852-2363 of TcdB receptor binding domain. The rTcdB was encapsulated in nanoparticles composed of γ-PGA and chitosan. Three rounds of intraperitoneal vaccination led to high anti-TcdB antibody responses and afforded mice full protection mice from lethal dose of C. difficile spore challenge. Protection was associated with high levels of toxin-neutralizing antibodies, and the rTcdB-encapsulated NPs elicited a longer-lasting antibody titers than antigen with the conventional adjuvant, aluminum hydroxide. Significant reductions in the level of proinflammatory cytokines and chemokines were observed in vaccinated mouse. These results suggested that polymeric nanocomplex-based vaccine design can be useful in developing vaccine against C. difficile infections.